Benefits and harms in pivotal trials of oral centrally acting antiobesity medicines: A systematic review and meta-analysis. - Onakpoya, I; Collins, D; Bobrovitz, N; Aronson, J; Heneghan, C (Wiley, 2018)
Objectives To evaluate the benefits and harms of oral centrally acting antiobesity medicinal products in pivotal trials. Methods The European Medicines Agency and Federal Drug Administration websites, PubMed, and ClinicalTrials. gov were searched to identify pivotal trials used to gain marketing authorizations. Pivotal phase III trials on which marketing authorizations were based were included. The data were analyzed by using Cochrane Review Manager (RevMan), and quality assessments for each outcome were performed by using the Grading of Recommendation, Assessment, Development, and Evaluation (GRADE). Results Five products (16 trials with 24,555 participants) were included. Significantly more participants who took the antiobesity products achieved ≥5% reduction in body weight (risk ratio [RR] 2.39; 95% CI: 2.09-2.74; GRADE5low). However, the products significantly increased the risk of adverse events (RR 1.12; 95% CI: 1.07-1.17; GRADE5very low) and the risk of discontinuation because of adverse events (RR 1.52; 95% CI: 1.33-1.74; GRADE5low). There were no significant differences for most outcomes between currently approved and withdrawn products. Conclusions Although oral centrally acting antiobesity products generate modest weight losses, they also increase the risks of adverse events and discontinuations because of adverse events. The premarketing benefit-to-harm profiles of currently available products and products that were later withdrawn because of harms are similar. Targeted study designs, better outcomes reporting, and improved postmarketing monitoring of harms are needed.